reviewing the OECD's and the EU’s assessment of Singapore's development and expansion incentive - BOULOGNE, Frederik (Institutional Knowledge at Singapore Management University, 2019)
This paper analyses and describes which norms can be derived from the OECD’s and the EU’s work on preventing harmful taxation that influence how Singapore should design and administer its Development and Expansion Incentive (‘DEI’). This analysis is relief upon in reviewing the Forum on Harmful Tax Practice’s conclusion that the DEI is not harmful and the decision not to place Singapore on the EU’s list of non-cooperative jurisdictions; a decision that suggests that the Council of the European Union considers Singapore to have adequately implemented the minimum anti-BEPS standards, of which BEPS Action 5 is one. These verdicts are, in the present author’s view, perfectly defensible, but they are nonetheless hard to justify on the basis of the criteria that were supposedly applied by the FHTP and the Council of the European Union. Particularly on the standards of ‘transparency’ and the ‘substantial activity requirement’ it seems difficult to conclude on the basis of the relevant legal provisions in, for instance, the Economic Expansion Incentives (Relief from Income Tax) Act (Chapter 86) or Singapore’s Income Tax Act, that the DEI is really sufficiently transparent and that the right substantial activities are required for the DEI. The present author, therefore, recommends the FHTP and the Council of the European Union to give much more insight as to why, and on which basis, the verdicts in the 2017 Progress Report were ultimately made and why the list of non-cooperative jurisdictions was drawn up as it was.